EFEKTIFITAS PEMBERIAN JUS BUAH NAGA TERHADAP IBU HAMIL DENGAN ANEMIA DI WILAYAH KERJA PUSKESMAS SELATBARU KECAMATAN BANTAN KABUPATEN BENGKALIS - Wisnututi, Wisnututi; Nadia, Fatma; Tanberika, Fajar Sari; Ekdeni Aifa, Wira (Ensiklopedia of Journal, 2025)
Anemia among pregnant women in Indonesia is still relatively high at 48.9%. Anemia itself can be prevented by consuming nutritious foods, one of which is dragon fruit. Red dragon fruit contains high potassium and flavonoids that can lower blood pressure. The purpose of this study was to determine the effectiveness of giving dragon fruit juice to pregnant women with anemia in the Selatbaru Health Center Working Area, Bantan District, Bengkalis Regency. This type of research is quasi-experimental with one group pre-test and post-test design. The sampling technique used Total Samples, namely sampling as a whole third trimester pregnant women as many as 20 respondents. The instruments used were the Easy Touch GCHb, SOP, and the observation bar. The intervention was given 2x in 1 day with a dose of 300 grams of dragon fruit plus 100 ml of water for 7 days. The results of analysis with paired t-test statistical test obtained p-value = 0.000 < α = 0.05. The conclusion is that there is an effect of giving dragon fruit juice to pregnant women with anemia. Suggestions for pregnant women are expected to diligently consume foods that contain iron, one of which is dragon fruit juice and be obedient in taking Fe tablets in order to increase Hb levels in the mother's blood.Keywords: Giving Dragon Fruit Juice, Hb Levels of Anemic Pregnant Women